2020
DOI: 10.3390/genes11010058
|View full text |Cite
|
Sign up to set email alerts
|

Biodosimetry of Low Dose Ionizing Radiation Using DNA Repair Foci in Human Lymphocytes

Abstract: Purpose: Ionizing radiation induced foci (IRIF) known also as DNA repair foci represent most sensitive endpoint for assessing DNA double strand breaks (DSB). IRIF are usually visualized and enumerated with the aid of fluorescence microscopy using antibodies to γH2AX and 53BP1. This study analyzed effect of low dose ionizing radiation on residual IRIF in human lymphocytes to the aim of potential biodosimetry and possible extrapolation of high-dose γH2AX/53BP1 effects to low doses and compared kinetics of DSB an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 47 publications
8
23
0
Order By: Relevance
“…Finally, dosimetry based on lymphocytes is still under investigation. One recent study on human lymphocytes showed that residual γ-H2AX and 53BP1 foci are very useful markers for biodosimetry [ 37 ]. We were interested in the characterization of the DDR in patients receiving PRRT with ( 177 Lu)Lu-DOTA-TATE beyond mere biodosimetry and its exploitation for a better understanding of the biology of the response to PRRT.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, dosimetry based on lymphocytes is still under investigation. One recent study on human lymphocytes showed that residual γ-H2AX and 53BP1 foci are very useful markers for biodosimetry [ 37 ]. We were interested in the characterization of the DDR in patients receiving PRRT with ( 177 Lu)Lu-DOTA-TATE beyond mere biodosimetry and its exploitation for a better understanding of the biology of the response to PRRT.…”
Section: Discussionmentioning
confidence: 99%
“…H2AX phosphorylation, mediated by ATM, ATR and DNA-PK sensor kinases, arises in response to DSBs formation and presents the evidence of their recognition [ 19 ]. 53BP1 is a p53 binding protein, which is a well known promoter of the DSB repair [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dose dependent formation of RIF of cH2A.X and 53BP1 in respect to foci numbers and intensity enables the quantification of signals. Therefore, both are commonly used biomarkers for evaluation of DSBs in radiation biology and are potentially suitable as a biodosimetric assay in accidental exposure (Jakl et al 2020).…”
Section: Introductionmentioning
confidence: 99%